(untitled) (The Research of Medical Science Review, 2025)
Background: Thyroid function is crucial for metabolic balance, and its assessment is vital in adolescents. Ultrasonography is a non-invasive tool that can evaluate thyroid parenchymal echogenicity, which may correlate with thyroid function. Objective: To correlate between thyroid parenchymal echogenicity and thyroid function tests among adolescents. Methods: A cross-sectional analytical design conducted at the radiology department of Allied Hospital Faisalabad, on 217 participants selected using a consecutive sampling technique, with inclusion criteria specifying adolescents aged 10 to 19 years who had undergone thyroid function tests (TSH, Free T4, and Free T3) within the last six months and had a thyroid ultrasound performed to assess parenchymal echogenicity. Exclusion criteria included clinically suspected thyroid nodules, previous thyroid surgery, and current use of thyroid medications. Ultrasound assessments were performed using Xario-100 and GE S-8 equipment with both convex and linear probes. Data was analyzed using SPSS 26. Results: The study included participants with a mean age of 14.45 years. TSH levels were significantly higher in females compared to males, with an overall average TSH level of 0.95 mIU/L. Free T4 and Free T3 levels remained within normal ranges, averaging 0.99 ng/dL and 2.50 pg/mL, respectively. The average thyroid volume was approximately 9.78 mL. In terms of thyroid echogenicity, participants were categorized into isoechoic, hyperechoic, and hypoechoic groups, with no statistically significant differences observed in thyroid function tests across these echogenicity types. Conclusion: Particularly with TSH levels, thyroid function tests and thyroid parenchymal echogenicity show a strong association among teenagers, this implies that evaluating thyroid condition in this age range can benefit much from ultrasonic imaging.